2018
DOI: 10.1038/s41419-018-0379-2
|View full text |Cite
|
Sign up to set email alerts
|

Redox metals homeostasis in multiple sclerosis and amyotrophic lateral sclerosis: a review

Abstract: The effect of redox metals such as iron and copper on multiple sclerosis and amyotrophic lateral sclerosis has been intensively studied. However, the origin of these disorders remains uncertain. This review article critically describes the physiology of redox metals that produce oxidative stress, which in turn leads to cascades of immunomodulatory alteration of neurons in multiple sclerosis and amyotrophic lateral sclerosis. Iron and copper overload has been well established in motor neurons of these diseases’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 221 publications
(224 reference statements)
2
57
0
Order By: Relevance
“…Throughout the prioritization process, we selected the ATP7A variant as a strong candidate for causing the disease. The ATP7A protein, a transmembrane P-type ATPase, has a wellcharacterized role in maintaining intracellular copper (Cu) concentrations, which are essential for regulating the activity of Cu-dependent enzymes that function in oxidation/reduction reactions, signaling pathways, and metabolism [34][35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the prioritization process, we selected the ATP7A variant as a strong candidate for causing the disease. The ATP7A protein, a transmembrane P-type ATPase, has a wellcharacterized role in maintaining intracellular copper (Cu) concentrations, which are essential for regulating the activity of Cu-dependent enzymes that function in oxidation/reduction reactions, signaling pathways, and metabolism [34][35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…This myelin protein is essential for neuronal function because of its support of the neuronal signal conduction without loss of strength. Whereas, the loss of myelin proteins by immunological abnormalities are cause the neuronal dysfunction and symptoms of MS. Further, these neuronal damages are permanent and difficult to the MS [78]. The symptoms of MS are numbness or weakness in limbs, one side of your body, legs and trunk; partial or complete loss of vision and double vision; tingling and pain; tremor, lack of coordination, unsteady gait, slurred speech, fatigue, dizziness; and bowel and bladder function.…”
Section: Role Of Lpo In Multiple Sclerosismentioning
confidence: 99%
“…Sometimes ALS is also produced in the lateral column degeneration with gliosis; so it is called "sclerosis". The primary etiology of ALS is due to the mutations of superoxide dismutase-1 (SOD1) gene [78]. The SOD gene associated proteins are responsible for the reduction of cellular free radicals leads to reduce the LPO products associated with protein and DNA damage [74,84].…”
Section: Role Of Lpo In Amylotropic Lateral Sclerosismentioning
confidence: 99%
“…It is well documented that cancer cells exhibit higher levels of oxidative stress than normal cells; therefore, an antioxidant system is expected to circumvent the growth of tumor cells …”
Section: Introductionmentioning
confidence: 99%
“…25,26 It is well documented that cancer cells exhibit higher levels of oxidative stress than normal cells; therefore, an antioxidant system is expected to circumvent the growth of tumor cells. [27][28][29][30][31] . Raffoul et al have recently shown that isoflavones such as genistein, daidzein, and glycitein exhibit anticancer properties, partially due to their antioxidant activities, as well as radio-sensitizers, which lead to the success of radiation-mediated suppression of the growth and metastatic potential of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%